2022
DOI: 10.3389/fneur.2022.899470
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 as a Predictive Biomarker for Collateral Formation Within Ischemic Moyamoya Disease

Abstract: ObjectiveMoyamoya disease (MMD) is a unique cerebrovascular occlusive disease characterized by progressive steno-occlusion within the terminal segment of the internal carotid artery. However, good collaterals from an external carotid artery are essential to compensate for the ischemia in moyamoya disease. This study aimed to investigate the transforming growth factor-beta 1 (TGFβ1) in plasma as a potential biomarker for predicting collateral formation in ischemic MMD.MethodsThe transcriptome profile downloaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[ 44 , 45 , 46 , 47 ]. Vascular endothelial growth factor (VEGF) and platelet-derived growth factor beta polypeptide b (PDGFbb) have been reported to be associated with MMD vessels and have even been applied to the generation of an MMD-like animal model [ 48 , 49 , 50 ]. Our results, for the first time, provide evidence that noncoding RNA circZXDC regulates the VSMC phenotype switch by sponging miR-125a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 , 45 , 46 , 47 ]. Vascular endothelial growth factor (VEGF) and platelet-derived growth factor beta polypeptide b (PDGFbb) have been reported to be associated with MMD vessels and have even been applied to the generation of an MMD-like animal model [ 48 , 49 , 50 ]. Our results, for the first time, provide evidence that noncoding RNA circZXDC regulates the VSMC phenotype switch by sponging miR-125a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively higher levels of TGFβ1 were observed in the plasma of ischemic MMD patients when compared to individuals with aneurysms and those who are in good health. This finding led to the conclusion that TGFβ1 plays a significant role in promoting collateral formation in ischemic MMD [6]. Cerebral angiography has played a critical role in the diagnosis and grading of MMD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to physiological angiogenesis, abnormal or pathological angiogenesis has been implicated in various neurological disorders, including MMD. Recent studies have shown that the dysregulation of angiogenic factors, such as vascular endothelial growth factor (VEGF), angiopoietin‐1, transforming growth factor‐beta 1 and platelet‐derived growth factor could cause abnormal angiogenesis in patients with MMD 6,7 . These angiogenic factors stimulate the proliferative and migratory abilities of ECs and pericytes and promote the production of extracellular matrix (ECM) proteins and new blood vessel formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the dysregulation of angiogenic factors, such as vascular endothelial growth factor (VEGF), angiopoietin‐1, transforming growth factor‐beta 1 and platelet‐derived growth factor could cause abnormal angiogenesis in patients with MMD. 6 , 7 These angiogenic factors stimulate the proliferative and migratory abilities of ECs and pericytes and promote the production of extracellular matrix (ECM) proteins and new blood vessel formation. However, the underlying mechanisms of the dysregulation of these angiogenic factors and the aberrant angiogenesis in patients with MMD are poorly understood.…”
Section: Introductionmentioning
confidence: 99%